Uso do levamisole como adjuvante no tratamento de mastite subclínica bovina - Enio Cesar Sarti (1993)
Levamisole was injected into 30 cows like adjuvant for the treatment of subclinical mastitis from dairy farm (Alfenas-MG). The efficacy was examined using the Califórnia Mastitis Test and suggestive identification of the etiologie agent. The cows with mastitis were treatment into two groups, in the lactating period, with levamisole and antibiotic or antibiotic and physiological salt solution. This fidings were not significative between treated group and control group, although the treated group has been apparent improvement.